INTONATION OF ENGLISH DECLARATIVE SENTENCE PRODUCED BY ENGLISH DEPARTMENT STUDENTS - Widagsa, Rudha (Universitas PGRI Yogyakarta, 2014)
Abstract This research is aimed at finding and describing the intonation of English declarative sentence produced by English Department students of Universitas PGRI Yogyakarta. The intonation is analyzed Â based on contour approach through the movements of pitch. The researcher uses three students as his respondents. The data are analized through three steps, firstly, data are collected through listening and recording process, secondly, the recording data are converted to soundwave and pitch diagrams using PRAAT software, at this point, PRAAT text grid is applied to make the pitch diagrams easy to understand, and finally, the researcher draws conclusion according to the contour of pitch in the diagrams.Â The result of this research illustrates that the respondents tend to rise the pitch at end of English declarative sentence which correspondingly changes the mood of the sentence into an interrogrative sentence. English declarative sentences generally have falling intonation and native speakers of English do not rise the pitch at the end of declarative sentences. However, this research shows that students of English have inadequate knowledge about suprasegmental features in English particularly intonation. Â Keywords: intonation, declarative, sentence